Finite Element Modelling of Structural Behavior of Precast Foamed Concrete Slab (PFC-CF-SF) Containing the Hybrid Fibers Under Flexural Load - George, Steafenie; Mohamad, Noridah (International Journal of Sustainable Construction Engineering and Technology, 2022)
Abstract: Reinforced concrete structure is inevitable from cracking. The material properties of the concrete itself, which is brittle, causing the concrete to have low tensile strength. Hybrid fibers that used in this study were coir fiber (CF) and steel fiber (SF). The purpose of the fibers was mainly to control the cracking of concrete. In view of this, a computational study was carried out to determine the structural behavior of Precast Foamed Concrete Slab (PFC-CF-SF) containing hybrid fibers under flexural load.  Parametric study of PFC-CF-SF with various slabâ€™s thicknesses and length was conducted. The slabs were subjected to flexure load until failure. The ultimate load, load-deflection midspan, and stress distribution of the slabs under flexure load were recorded. To validate the slab model using finite element analysis (FEA) in ABAQUS software, the results recorded from finite element model simulation was compared with the experimental results. From FEA, the result of PFC-CF-SF slab and experimental work was validated with difference of 6.13% ultimate load, and 7.01% difference in load deflection midspan which is in acceptable range of Â±10%. The parametric studies of PFC-CF-SF with different length and thickness showed decreasing value of ultimate load capacity and higher deflection with the increment of length. Despite that, an increasing of ultimate load value and declining of deflection was showed with the increasing of slabâ€™s thickness. This study proved that PFC-CF-SF was more ductile than plain foamed concrete with higher ultimate load bearing capacity and the usage of fibers in foamed concrete slab was able to control the crack propagation.